Удаан нейтроноор явагдах (n,α) урвалын дундач огтлол - Г, Хүүхэнхүү; И, Чадраабал (Scientific transaction of the National University of Mongolia. Physics, 2022)
For average (n,a) cross section of slow neutrons were obtained working formulae based on the statisticaI model. As example, for several target nuclei with A = 91 - 149 were calculated the transmission factors of a particle.